Life of a Wildflower: Reimagining Meaningful Learning Through Play-Based Pedagogy (LEARNing Landscapes, 2021)
The author explores tensions between teacher-centered styles of teaching and play-based approaches that invite students to be creators of their own learning. Through narrative inquiry, the author uses a metaphor of wildflowers growing in natural environments to explore a child-led process of learning through play that fosters creativity and deep thinking. Teaching Kindergarten for the first time, the author reflects on challenges of living “secret stories” in the classroom that differ from “sacred stories” of the school’s pedagogical practices, feeling a need to create a “cover story” to present her pedagogy as conforming, yet capable and successful.
Keywords: play-based pedagogy; early learning; secret, sacred and cover stories; narrative inquiry